Autoregression filters for interference suppression in atmosphere acoustic sounding systems - Карташов, В.М.; Тихонов, В.А.; Воронин, В.В.; Селезнев, И.С. (Radiotekhnika, 2019)
The models of autoregression are built and parametric spectra of acoustic noise, which take place during the operation of acoustic sounding systems in conditions of airport operation, are analyzed. Special attention is paid to the synthesis of autoregressive prediction filters for interference suppression. The values of the suppression coefficients are obtained by autoregressive filters for predicting acoustic noise generated by airplanes.